Exploring commercial contingency environmentdevelopmental factors affecting the adoption of mobile payment: a qualitative study - Manoharan, Sharmila; Rahman, Rozanah Ab.; Bakar, Elistina Abu; Hashim, Haslinda; Subramaniam, Shamala (Malque Publishing, 2024)
This qualitative study explores the changes in the commercial environment as external changes impact mobile customer payment (mPayment) adoption from the service provider based on Contingency Theory (CT) underpinnings. To test the objectives, data was collected from semistructured personal interviews using a small group of imminent participants and was analyzed using phenomenological research to yield rich data beyond customer adoption. This study employed the CT and Technology Acceptance Model (TAM) theory to provide in-depth commerce environment contribution factors. These external factors that impact mobile payment adoption from the service provider act as the key driving force in the value chain. Often arising from market dictatorship beyond the service provider's control. This study accumulated data to elucidate Research Question One (RQ1): What are the market developments in the commerce environment influencing mPayment?. The findings indicated that the commerce environment market development branches into three categories: Commercial Environment Development, Commercial Policy Development, and Commercial Trends Development. The characteristic of the mobile payment service market implicates value to customer adoption beyond the ability of the service providers to dictate. The three categories under the mPayment commerce environment market development contributed to the body of knowledge: 1) Commercial Environment Development: affirms the positive mPayment dynamics and progressively visible developmental changes; 2) Commercial Policy Development: allows both service provider and consumer to make an informed decision related to mPayment transactions as it influences the operational frameworks of the consumer; 3) Commercial Trends Development: provides strategic directions to the service providers in the future.